2015
DOI: 10.1039/c5ra05061h
|View full text |Cite
|
Sign up to set email alerts
|

The distinct role of the flexible polymer matrix in catalytic conversions over immobilised nanoparticles

Abstract: Polymer resins with immobilized metal nanoparticles represent highly promising materials for attaining intelligent and ecologically friendly catalysts. Control of the dynamic swelling behaviour of the polymer resins enables the on/off-switching of the activity of the encapsulated metal nanoparticles, thereby allowing conversion and selectivity to be controlled at a specific time of the chemical reaction. This paper presents a study on the distinct role of the polymer support. Here, the hydrogenation of nitrobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Thus, cellulose is converted to polyols over ruthenium supported on crosslinked polystyrene [149,151]. Swelling of the polymer [152] thereby facilitates access of the substrate to the catalytic sites.…”
Section: Ruthenium Catalysts In Cellulose Conversionmentioning
confidence: 99%
“…Thus, cellulose is converted to polyols over ruthenium supported on crosslinked polystyrene [149,151]. Swelling of the polymer [152] thereby facilitates access of the substrate to the catalytic sites.…”
Section: Ruthenium Catalysts In Cellulose Conversionmentioning
confidence: 99%
“…Moreover, it has already been reported that in resin catalysts, additional functional groups can favor the adsorption of the reagents with no appreciable increase of their swelling degree ("assisted adsorption"), provided they have some kind of affinity towards the molecules of the reagents. In that case, the "assisted adsorption" was based on hydrophobic interaction [50][51][52]. It can be therefore argued that also in AME 40-40 and AME 45-40 there is an "assisted adsorption" of the β-(1,4)-glucans sustained by the interactions of their molecules with hydroxyl and carboxylic groups.…”
Section: Catalytic Hydrolysismentioning
confidence: 99%